Preventive non–pharmacological treatment and nitric oxide in chronic migraine - Ciancarelli, I. (Springer-Verlag, 2005)
In chronic migraine the central sensitisation and the changes of regional cerebral blood flow are mediated by nitric oxide (NO) and oxygen free radicals. Biofeedback is considered a preventive non–pharmacological treatment decreasing migraine attacks. We investigated whether biofeedback effectiveness is related to relaxation processes and its influence on oxidative stress. The Migraine Disability Assessment Score (MIDAS) and serum NO stable metabolites (NO(x)) were evaluated in 20 patients with chronic migraine before and at the end of biofeedback sessions. MIDAS score was lower after biofeedback than that reported before treatment. NO(x) serum levels were higher after biofeedback than those measured before starting treatment. Thus, the effectiveness of biofeedback is related to a muscular relaxation and to its influence on NO bioavailability in patients with chronic migraine.